Diagnostic performance of two different maternal near-miss approaches in a High Obstetric Risk Unit. Issue 8 (14th September 2021) - Escobar, María; Mosquera, Claudia; Hincapie, María Antonia; Nasner, Daniela; Carvajal, Javier Andrés; Maya, Juliana; De Mucio, Bremen; Sosa, Claudio Gerardo; Rojas, José Antonio
ABSTRACT: Maternal near-miss (MNM) is a maternal quality care indicator. The World Health Organization (WHO) defines it as a state in which a woman nearly dies but survives due to a complication during pregnancy, birth, or puerperium. The Latin American Federation of Obstetrics and Gynecology (FLASOG) and the Colombian National Health Institute (INS) established recommendations for the event's epidemiological surveillance; nonetheless, the operational definitions of the cases are different. This retrospective study examined the approaches of FLASOG and INS versus the WHO approach (gold standard) for the assessment of MNM in a high obstetric risk unit. Patients admitted with at least one criterion of the WHO, FLASOG, or INS approach for the definition of MNM from March 2016 to March 2017 were included. Sensitivity, specificity, positive and negative predictive value (PPV, NPV) were evaluated, as well as the Receiver Operating Characteristics (ROC) curve of the FLASOG and INS. MNM classification compared to WHO system as reference. The results highlight that the WHO classification establishes very high boundaries for some of the diagnostic criteria and the lack of standardization of the MNM criteria among the different proposals in Latin America hinders the applicability in Colombia and other countries with a similar situation. Graphical abstract: uf0001